Psychopathy and Reoffending Among Incarcerated Women - Pinheiro, Marina (Women & criminal justice, 2022)
Several studies found that psychopathy is an important predictor of general reoffending/recidivism. However, these conclusions are often based on male samples. This study analyzes the association between psychopathic traits and the four facets of psychopathy (i.e., interpersonal, affective, lifestyle, antisocial) and general reoffending among incarcerated women. The Psychopathy Checklist-Revised (PCL-R) was applied to a sample of 63 incarcerated women from Portugal who were retrospectively classified as committed repeated versus first-time offenses. Two separate binary logistic regression analyses were conducted, controlling for age and criminal variables. PCL-R total scores did not postdict reoffending, but sentence length did. As for the four facets, only PCL-R antisocial facet postdicted reoffending. Sentence length was also negatively associated with reoffending. Despite the relationship between PCL-R antisocial facet and general reoffending, results raise some questions regarding the applicability of psychopathy construct in the prediction of reoffending among women.